International Regulation of Gene Editing Technologies in Crops Current Status and Future Trends - Clark, Lisa F.; Hobbs, Jill E.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book analyzes the regulation and governance of gene editing in the global agrifood system as applications of gene editing, regulations and the intellectual property landscape continue to evolve. The primary focus of the manuscript is the dynamic interactions between regulatory frameworks and agricultural applications of gene editing in plant breeding. The goal is to give readers a holistic perspective on why the status of gene editing in agricultural applications is in a state of flux in some jurisdictions (e.g., the European Union) while more settled in others (e.g., Canada). Readers are provided with a clearer picture of what the future might hold for the use of gene editing in agriculture as a means to address food insecurity as the climate crisis grows and amid global geopolitical and economic turbulence.
Part 1 Balancing Innovation -- Chapter 1 Introduction -- Chapter 2 What is Gene Editing? -- Chapter 3 How are Gene Editing Technologies Regulated in the Agrifood System? -- Part 2 Emerging Opportunities for Regulatory Enhancement -- Chapter 4 Novel Genomic Techniques and Applications on the Horizon -- Chapter 5 Governing the Unknown -- Chapter 6 What$1 (Bs Next for Gene Editing in Agrifood?.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Environment; Agriculture -- Economic aspects; Agricultural genome mapping; Agricultural biotechnology; Environmental Sciences; Agricultural Economics; Agricultural Genetics; Agricultural Biotechnology